Strategic site selection methodology for small modular reactors: A case study in Türkiye - Ayyildiz, Ertugrul; Yildirim, Betul; Erdogan, Melike; Aydin, Nezir (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Selecting the optimal site for Small Modular Reactors (SMRs) ensures operational efficiency and safety and aligns with growing energy demands and environmental goals. Given the unique challenges of climate change and the need for sustainable energy solutions, this study's innovative approach provides critical insights for making informed decisions that balance economic, environmental, and social factors. This study introduces a novel hybrid multi-criteria decision-making (MCDM) approach for selecting optimal sites for SMR in T & uuml;rkiye. The proposed methodology integrates Picture Fuzzy SWARA (PiF-SWARA) and Picture Fuzzy WASPAS (PiF-WASPAS) techniques to address site selection's complexities by evaluating criteria weights and alternative scores. PiFSWARA is employed to determine the relative importance of five main criteria and 28 sub-criteria, providing a nuanced understanding of each criterion's impact. Subsequently, PiF-WASPAS ranks the alternative sites based on these weighted criteria. This approach ensures a robust evaluation by accommodating various uncertainties inherent in the decision-making process. The case study applied to T & uuml;rkiye demonstrates the effectiveness of this method in identifying the most suitable locations for SMRs, highlighting its potential to advance the strategic planning of nuclear energy infrastructure. The study provides valuable insights for policymakers and stakeholders involved in energy planning and development.
Keywords: Multi-criteria decision making; Picture fuzzy set; Site selection; Small modular reactor; Sustainability; THERMAL PLASMA TECHNOLOGY; NUCLEAR-POWER-PLANT; AGGREGATION OPERATORS; FUZZY; ENVIRONMENT; Science & Technology - Other Topics; Energy & Fuels